Phosphorylation Dynamics within Intrinsic Disordered Regions of ORF4 Protein in HEV - Shafat, Zoya (Shedding Light on the Open Reading Frame 4 of Hepatitis E Virus - Molecular, Evolutionary & Genetic Aspects, 2024)
Hepatitis E Virus (HEV) is a single-stranded RNA virus. The phosphorylation patterns in HEV ORF4 remain unelucidated. As phosphorylation regulates the activity in proteins, thus the identification of phosphorylation sites (P-sites) in HEV ORF4 protein is much needed. Herein, we report the prediction of P-sites in ORF4 proteins by employing a web-based server with improved accuracy. Comparative analysis revealed the prevalence of P-sites within intrinsically disordered regions of ORF4. It was observed that the composition of amino acid residues surrounding P-sites was enriched in disordered-promoting residues in ORF4. The occurrence of P-sites within the identified protein’s disordered regions in conjunction with subsequent enrichment in disordered residues around P-sites suggests a tight interconnection between protein phosphorylation and disorder. The presented study is aimed to provide insights regarding the role of disorder in protein phosphorylation.